Identification of a Lactate-Quinone Oxidoreductase in Staphylococcus aureus that is Essential for Virulence - Fuller, James R.; Vitko, Nicholas P.; Perkowski, Ellen F.; Scott, Eric; Khatri, Dal; Spontak, Jeffrey S.; Thurlow, Lance R.; Richardson, Anthony R. (Frontiers in Cellular and Infection Microbiology, 2011)
Staphylococcus aureus is an important human pathogen commonly infecting nearly every host tissue. The ability of S. aureus to resist innate immunity is critical to its success as a pathogen, including its propensity to grow in the presence of host nitric oxide (NO·). Upon exogenous NO· exposure, S. aureus immediately excretes copious amounts of L-lactate to maintain redox balance. However, after prolonged NO·-exposure, S. aureus reassimilates L-lactate specifically and in this work, we identify the enzyme responsible for this L-lactate consumption as a L-lactate-quinone oxidoreductase (Lqo, SACOL2623). Originally annotated as Mqo2 and thought to oxidize malate, we show that this enzyme exhibits no affinity for malate but reacts specifically with L-lactate (KM = 330 µM). In addition to its requirement for reassimilation of L-lactate during NO·-stress, Lqo is also critical to respiratory growth on L-lactate as a sole carbon source. Moreover, ∆lqo mutants exhibit attenuation in a murine model of sepsis, particularly in their ability to cause myocarditis. Interestingly, this cardiac-specific attenuation is completely abrogated in mice unable to synthesize inflammatory NO· (iNOS-/-). We demonstrate that S. aureus NO·-resistance is highly dependent on the availability of a glycolytic carbon sources. However, S. aureus can utilize the combination of peptides and L-lactate as carbon sources during NO·-stress in an Lqo-dependent fashion. Murine cardiac tissue has markedly high levels of L-lactate in comparison to renal or hepatic tissue consistent with the NO·-dependent requirement for Lqo in S. aureus myocarditis. Thus, Lqo provides S. aureus with yet another means of replicating in the presence of host NO·.